Diffuse Hepatic FDG Activity From Nonmalignant Etiologies. (July 2015) - Huo, Li; Zheng, Youjing; Li, Fang
Abstract : Abstract: Diffuse increased 18 F-FDG activity is commonly caused by malignant involvement. We describe here cases of diffuse, uniformly increased 18 F-FDG activity due to nonmalignant illnesses in 2 patients: one had parvovirus B19 infection, whereas the other had porphyria, a heme synthesis disorder.